Superionic conduction in β-eucryptite: inelastic neutron scattering and computational studies12. Issue 23 (5th June 2017) - Singh, Baltej; Gupta, Mayanak Kumar; Mittal, Ranjan; Zbiri, Mohamed; Rols, Stephane; Patwe, Sadequa Jahedkhan; Achary, Srungarpu Nagabhusan; Schober, Helmut; Tyagi, Avesh Kumar; Chaplot, Samrath Lal
Abstract : The inter- and intra-channel correlated motion of lithium along the hexagonal c -axis gives the minimum energy pathway for ion conduction. Abstract : β-Eucryptite (LiAlSiO4 ) is known to show super-ionic conductivity above 700 K. We performed inelastic neutron scattering measurements in β-eucryptite over 300–900 K and calculated the phonon spectrum using classical molecular dynamics (MD) simulations. The MD simulations were used to interpret the inelastic neutron spectra at high temperatures. The calculated diffusion coefficient for Li showed superionic conduction above 1200 K in the perfect crystal. The presence of defects was found to enhance diffusion and lower the temperature for Li diffusion. The calculated trajectory of Li atoms at higher temperatures shows that preferential movement of the Li atom is along the hexagonal c -axis, which is further confirmed by the ab initio calculated activation energy profile for cooperative lithium ion displacements. The inter- and intra-channel correlated motion of Li along the hexagonal c -axis gives the minimum energy pathway for Li ion conduction in LiAlSiO4 .